Rasmussen aneurysm: A forgotten complication of tuberculosis in the COVID-19 era. (2022) - Mahmoud, N.; Moussa, C.; Attia, M.; Rouis, H.; Khattab, A.; Khouaja, I.; Zendah, I.; Hantous, S.; Maȃlej, S.
Abstract: COVID-19 pandemic has led to an overwhelming healthcare system causing a delay in management of other infectious diseases such as tuberculosis. Rasmussen aneurysm (RA) appears in chronic cavitary tuberculosis. We report here, three cases of pulmonary tuberculosis complicated by RA admitted to Department 1 of Abderrahmane Mami hospital in Tunisia. Data were collected from June 2020 to September 2021. All patients presented with hemoptysis. Sputum was positive for the acid-fast bacilli. Computed tomographic pulmonary angiography showed RA. Only one patient underwent emergent glue embolization. These cases give an insight into the importance of timely therapeutic care for tuberculosis.